La relación entre el ambiente escolar y el ciberacoso. Un estudio narrativo en una institución educativa del municipio de Soacha - Patiño Reyes, Zenayda (Universidad Antonio Nariño, 2024)
The narrative research carried out in an educational institution in the municipality of Soacha sought to understand how the school environment influences the cases of cyberbullying suffered by high school students. The research was divided into two phases: in the first, two surveys on the school environment and the use of social networks were applied to 216 tenth and eleventh grade students; In the second, 15 participants, including a teacher, were selected to narrate their experiences of cyberbullying.